The Intersection of Cross-Cultural Adaptation of Balinese and Digital Nomads - Tenaya, Luh Made Kirana Medhawi; Husain, A. Hasan Al (PT FORMOSA CENDEKIA GLOBAL, 2024)
The adaptation of Balinese society to the presence of digital nomads involves a complex process of cross-cultural communication that extends beyond cultural aspects alone. The ways in which digital nomads and local residents interact and understand each other are influenced by various communication patterns they employ. Cultural differences, social norms, and language barriers impact how these two groups communicate. This research aims to provide a deeper understanding of how the Balinese society adapts to the presence of digital nomads, viewed through the lens of Young Yun Kim's cross-cultural adaptation theory. The research method used in this study is qualitative research. In conclusion, the cross-cultural adaptation between the Balinese society and digital nomads demonstrates that both groups can create a harmonious and mutually beneficial environment through open communication, mutual understanding, and a willingness to adapt